1977
DOI: 10.1007/bf01531111
|View full text |Cite
|
Sign up to set email alerts
|

A dermatoglyphic study of autistic patients

Abstract: Dermatolglyphic patterns of autistic children were compared to those of control subjects matched socioeconomically and by age and sex. Analysis of dermal ridge patterns and ridge counts resulted in significant differences between the 78 autistic and 78 normal children. Differences from normal expectation in the autistic children were most apparent in the reduced number of whorls and increased number of arches, in lowered ridge counts, and in less distinctness in formation of ridge line. The number of dermal ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…ASD in this paper is used as an umbrella term and refers to autistic disorder, Asperger syndrome, and Pervasive Developmental Disorder Not Otherwise Specified (PDD-NOS). Children with ASD were found to have more arches and fewer whorls than typically developing (TD) children [ 32 ]. A study of children with intellectual disability (ID) also found more arches, the simplest fingerprint pattern, and more abnormal PFC patterns [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASD in this paper is used as an umbrella term and refers to autistic disorder, Asperger syndrome, and Pervasive Developmental Disorder Not Otherwise Specified (PDD-NOS). Children with ASD were found to have more arches and fewer whorls than typically developing (TD) children [ 32 ]. A study of children with intellectual disability (ID) also found more arches, the simplest fingerprint pattern, and more abnormal PFC patterns [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study of children with intellectual disability (ID) also found more arches, the simplest fingerprint pattern, and more abnormal PFC patterns [ 33 ]. Palmar atd-angles are smaller in patients with ASD compared to TD children (e.g., [ 32 ]). Not all studies, however, agree on this finding [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…They evaluated 100 autopsies and found that length of right hand life line and age at death were statistically correlated even though according to Karnick, person's longevity is influenced by the heart line. 1,19 Various other studies have associated dermatoglyphic patterns with dental caries, 20 gynecological cancers, 21 autism, 22 nonsyndromic cleft lip, 23 and breast cancer. 24,25 In current study, the palmist took into consideration the color pattern, tone of palm, as well as skin pattern of palm in predicting the survival and condition of patient.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of atypical patterns are single transverse crease in the hand palm, and an arch-like fingerprint patterns (Scott et al, 2005;Vormittag, Weninger, Hollmann, & Hoffmann, 1979;Woolf & Gianas, 1976). These atypical patterns are also more common in other congenital disorders such as Down's Syndrome and autism (Dar, Schmidt, & Nitowsky, 1977;Walker, 1977). The observation of abnormalities in hair and teeth in congenital disorders that affect the brain can be explained by the shared ectodermal origin of all these organs.…”
Section: Embryology Of Isolated Cleft Lip And/or Palatementioning
confidence: 98%
“…On the other hand, malformations that affect both the CNS and the urinary system are relatively rare (Mueller, et al, 2007). It is therefore common to see patients with congenital brain malformations to present with a number of abnormalities such as closely spaced eyes (i.e., hypotelorism) (DeMyer, 1975;Demyer, Palmer, & Zeman, 1964), abnormalities in the number of digits (e.g., Cornelia de Lange syndrome) atypical fingerprint patterns (i.e., dermatoglyphics) (Walker, 1977) and unusual hair growth and color, such as atypical hair whorls (Furdon & Clark, 2003).…”
Section: Embryology Of Isolated Cleft Lip And/or Palatementioning
confidence: 99%